Experimental investigation on the effect of nanostructuration on the adherence properties of epoxy adhesives by a probe tack test. (June 2016) - Tramis, O.; Brethous, R.; Hassoune-Rhabbour, B.; Fazzini, M.; Nassiet, V.
Abstract: In this work, we aimed to characterize the energy of adherence of nanoscale structured epoxy adhesives Diglycidyl ether of bisphenol-A/Methylene–diethylaniline (DGEBA/MDEA) induced by phase separation triblock copolymers Poly (Methacrylate de Methyl)-b-Poly (Butyl Acrylate)-b-Poly (Methyl Methacrylate) (PMMA-b-PBA-b-PMMA) at gel state by a probe tack test, which is an original use of this kind of test for thermoset adhesives. For a set of mechanical parameters (probe's roughness, contact time, contact pressure and debonding velocity), we measured the energy of adherence for both neat and filled adhesives. The probe tack test was performed at different steps of gelation. We compared the behavior of the adhesives and evaluated the dissipation contribution to the energy of adherence of the adhesives during the test. We finally discussed the nanoparticles׳ influence on the competition between cavitation and fibrillation. We report that the addition of nanoparticles leads to an overall improvement of the energy of adherence, with a significant increase of the dissipation contribution to the energy measured.